Who Manages Risk? An Empirical Examination of Risk Management Practices in the Gold Mining Industry. - Tufano, Peter (Journal of Finance, 1996)
This article examines a new database that details corporate risk management activity in the North American gold mining industry. The author finds little empirical support for the predictive power of theories that view risk management as a means to maximize shareholder value. However, firms whose managers hold more options manage less gold price risk, and firms whose managers hold more stock manage more gold price risk, suggesting that managerial risk aversion may affect corporate risk management policy. Further, risk management is negatively associated with the tenure of firms' CFOs, perhaps reflecting managerial interests, skills, or preferences.